Association Between Macroorchidism and Intelligence in FMR1 Premutation Carriers - Lozano, Reymundo (Am J Med Genet A, 2014)
Characteristics of fragile X syndrome include macroorchidism and intellectual disability, which are associated with decreased FMRP levels. FMRP is highly expressed in many tissues, but primarily in the brain and testis. The relationship between these two characteristics has not previously been studied in the premutation or carrier state. To examine this among premutation carriers and a possible association with IQ, we evaluated macroorchidism status among 213 males including 142 premutation carriers and 71 controls. The prevalence of macroorchidism among premutation carriers was 32.4% (46 out of 142), and 5.6% among controls (4 out of 71, P <0.0001). Among premutation carriers, the age-adjusted odds ratio (OR) of macroorchidism was significantly increased with increasing FMR1 mRNA (OR 1.84, 95% confidence interval [CI] 1.04–3.25; P 0.035). With respect to the association between macroorchidism and IQ, after adjustment for number of CGG repeats and age, premutation carriers with macroorchidism had lower verbal IQ (104.67±15.86, P 0.0152) and full scale IQ (102.98±15.78, P 0.0227) than premutation carriers without macroorchidism (verbal IQ 112.38 ±14.14, full scale IQ 110.24±14.21). Similar associations were observed for both verbal IQ (P 0.034) and full scale IQ (P 0.039) after being adjusted for age and FMR1 mRNA. These preliminary data support a correlation between macroorchidism and lower verbal and full scale IQ in a relevant proportion of premutation carrier males. Whether this is due to higher levels of FMR1 mRNA or to lower FMRP levels it remains to be established.